Sosialisasi Hukum Perbankan Pembiayaan Kredit Usaha Rakyat (KUR) Bagi Pengembangan UMKM di Desa Kalidungjaya Karawang - Fadhilah, Meita; Setiady, Tri; Tahir, Erdin (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
The People's Business Credit Program is one of the government's programs to increase access to financing for Micro, Small, and Medium Enterprises (MSMEs) which is channeled through financial institutions with a guarantee pattern. The financing distributed by people's business credit comes from banking funds or financial institutions that are people's business credit distributors. The funds provided are in the form of working capital and investment funds which are distributed to individual/individual MSMEs, business entities, and/or business groups who have productive and viable businesses but do not have additional collateral and also do not have good financial records. Even though the government has provided large MSME funds, the public is still unaware of people's business credit distribution. The people's business credit program is still the spearhead of government programs in efforts to expand access to financing for micro, small, and medium enterprises. The main aim of implementing this socialization is for the community to be able to develop their business into a bigger one, have business activities with good financial reports, and have no doubts about applying for people's business credit to the nearest state-owned bank to expand their business.